Теоретико-методологічний підхід до аналізу професійного потенціалу професорсько-викладацького складу вищого навчального закладу - Тугай, А. М.; Гойко, А. ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2014)
A theoretical and methodological approach to the analysis of the professional capacity of higher education institutions (HEIs) in general through the assessment of the potential of each teacher on the results of its operations.